Arginine depletion as a therapeutic approach for patients with COVID-19 - Grimes, Joseph M.; Khan, Shaheer; Badeaux, Mark; Rao, Ravi M.; Rowlinson, Scott W.; Carvajal, Richard D. (International journal of infectious diseases, 2021)
•Arginine is a key nutrient shown to be essential in the life cycle of many viruses.•Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) replication relies on conserved arginine residues.•Arginine depletion may also reduce inflammation in COVID-19 patients.•Clinical stage arginine-depleting enzymes could be trialed in COVID-19 patients. The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a source of significant morbidity and death worldwide, and effective treatments are urgently needed. Clinical trials have focused largely on direct antiviral therapies or on immunomodulation in patients with severe manifestations of COVID-19. One therapeutic approach that remains to be clinically investigated is disruption of the host-virus relationship through amino acid restriction, a strategy used successfully in the setting of cancer treatment. Arginine is an amino acid that has been shown in nonclinical studies to be essential in the life cycle of many viruses. Therefore, arginine depletion may be an effective therapeutic approach against SARS-CoV-2. Several arginine-metabolizing enzymes in clinical development may be a viable approach to induce a low arginine environment to treat COVID-19 and other viral diseases. Herein, we explore the rationale for arginine depletion as a therapeutic approach for COVID-19.